Efektivitas Konsorsium Mikroba Pelarut Fosfat Lokal dalam Formulasi Pupuk Cair Organik terhadap Pertumbuhan Cabai Rawit - Kussani, Taofi; Juita Fahrani (Insight of Biology, 2025)
Declining soil fertility and limited phosphorus availability are key constraints to enhancing the productivity of bird’s eye chili (Capsicum frutescens L.) cultivation. Although phosphorus is present in the soil, much of it exists in insoluble forms, rendering it inaccessible to plants. This study aimed to assess the efficacy of a locally sourced phosphate-solubilizing microbial (PSM) consortium, formulated into an organic liquid fertilizer (OLF), in promoting the growth of bird’s eye chili. The PSM consortium, composed of Bacillus sp., Pseudomonas sp., and Aspergillus sp. isolates obtained from local agricultural soils, was incorporated into an OLF derived from liquid organic waste. A completely randomized design (CRD) was employed with five treatment groups: a non-fertilized control, OLF without PSM, and three concentrations of PSM-enriched OLF. Growth parameters including plant height, leaf number, and biomass weight were measured at 40 days after planting. Results revealed that application of the PSM-enriched OLF significantly enhanced plant growth compared to both the control and the non-inoculated OLF treatment (p < 0.05). The most effective treatment was a 20% concentration of PSM-enriched OLF, which increased plant height by 32.5%, leaf number by 28.4%, and fresh biomass weight by 35.1% relative to the control. These findings underscore the potential of combining organic liquid fertilizer with indigenous phosphate-solubilizing microbes to improve phosphorus bioavailability and support crop growth. This biofertilizer formulation represents a promising, environmentally sustainable alternative for enhancing soil fertility and promoting sustainable agricultural practices.